INTEGRATION OF THEORY AND PRACTICE IN TRAINING ELECTRICIAN SPECIALISTS - Rizoyev Sirojiddin Sano o‘g‘li (TADQIQOTLAR, 2026)
Abstract This article discusses the importance of integrating theoretical knowledge and practical skills in the training of electrician specialists in vocational education institutions. Effective professional activity in the electrical field requires students to master both the theoretical principles and practical skills. The study examines the interrelation between physics and specialized technical subjects, as well as the role of laboratory work and industrial practice in developing professional competencies. Furthermore, the article explores modern pedagogical technologies to strengthen the integration of theory and practice in vocational education.